Indicação geográfica e redes espaciais da produção cafeeira no cerrado mineiro: um estudo da Região de Patrocínio, MG - Oliveira, Ramon de Souza (Universidade Federal de Catalão, 2018)
The main objective of this research is to present and understand the process of formation of the spatial circuit of coffee production in the area delimited by the Geographical Indication of the Cerrado Mineiro Region, in the State of Minas Gerais (MG). The loci of investigation of the present research is the municipality of Patrocínio MG, current administrative city of the Denomination of Origin (D.O) and the Indication of Origin (I.P) of the Cerrado Mineiro Region for the coffee product. Currently, all the production, flow and distribution logistics, marketing and digital marketing strategies and strategic planning for the development and structuring of the globalized scientific coffee growing IG in the Cerrado Mineiro Region are concentrated in this city. The total planted area of coffee in this municipality in 2018 is 183,502.0 ha with an average production of around 56,607,000 million bags of 60 kg. For more than a decade, the municipality of Patrocínio has been in the first position in the national ranking of the largest Brazilian coffee-producing municipalities and with the largest production area destined for the cultivation of this commodity. In order to better achieve the proposed objective, the methodological procedures adopted are based on theoretical and documentary research aimed at presenting and attesting to the concepts related to the modernization of agriculture, globalized scientific agriculture, logistics, spatial production circuit, geographical indications, among other relevant topics. Currently, this coffee growing municipality has a denomination of origin for the coffee product, and is consolidated as a management model, use of technology and quality and diversity certification for Brazilian agri-food products.
Keywords: Indicação Geográfica; Redes Espaciais; Café; Cerrado Mineiro; Patrocínio (MG); 7.06.01.02-0